Learning symbols from permanent and transient visual presentations: Don't overplay the hand. (January 2018) - Castro-Alonso, Juan C.; Ayres, Paul; Wong, Mona; Paas, Fred
Abstract: Instructional dynamic pictures (animations and videos) contain transient visual information. Consequently, when learning from dynamic pictures, students must process in working memory the current images while trying to remember the images that left the screen. This additional activity in working memory may lead dynamic pictures to be less suitable instructional materials than comparable static pictures, which are more permanent. In order to directly show the influence of transient visual information on dynamic learning environments, we designed a well-matched comparison between a permanent and a transient presentation of an abstract-symbol memory task on the computer. In the task, 104 university students (50% females) had to memorize the type, color, and position of the symbols in a rectangular configuration. In addition, an embodied cognition factor was included where the symbols in the task were either shown with a precision grasping static hand or not. We also assessed how individual characteristics (spatial ability, spatial memory span, and gender) influenced performance. Results showed that (a) permanent outperformed transient presentations, (b) observing hands hindered learning, and (c) high spatial ability and high spatial memory span were beneficial, but gender did not affect performance. Highlights: University students attempted computer tasks of learning abstract symbols. Well-controlled within-subjects statics vs. animation comparisons were conducted. Learning the symbols was lower for animations compared to statics. Showing hands in a precision posture near the symbols was counterproductive. Spatial ability and spatial memory span, but not gender, affected performance.